Evaluation of Optical Properties of Different Restorative Composite Resins - Raquel Pachaly; Manuela Batistella Zasso; Mariah Bonilha Silveira; Roselaine Terezinha Pozzobon (Revista da Faculdade de Odontologia de Porto Alegre)
The esthetic demands of patients have encouraged the search for restorative materials increasingly similar to natural teeth. This requires knowledge on the optical properties of dental structures and restorative materials. This study comparatively evaluated the translucency/opacity and fl uorescence of different brands of composite resins. Sixteen brands of composite resins shade A2 were randomly selected; specimens with 1mm thickness and 10mm diameter were fabricated with these resins and evaluated as to the optical properties, scored as high, medium and low translucency/opacity and fl uorescence. Statistical analysis by the Kendall W test and Friedman test at a signifi cance level of 5% revealed that the resins Opallis D, Four Season D, Concept E, Concept D, and FillMagic presented low translucency. Conversely, the resins Opallis E, Charisma, Tetric Ceram, Four Season E, Natural Look, Z350, and Z250 exhibited medium translucency/opacity, and resins Nova Charisma, Durafi ll, and Supreme XT presented high translucency. With regard to fl uorescence, the resins Charisma, Z350, Supreme XT, and Z250 present low fl uorescence. Medium fl uorescence was observed for the resins Opallis E, Opallis D, Nova Charisma, Durafi ll, Natural Look, TPH Spectrum, Tetric Ceram, Four Season E, and Four Season D. The composite resins Concept E, Concept D, and Fill Magic presented high fl uorescence. Based on these results, it is concluded that there are differences in the degree of translucency/opacity and fl uorescence of different composite resins, which are possibly related to variations in their composition.